Legal Reform for the Fulfilment of Disabilities Human Rights - Suwandoko Suwandoko; Satrio Ageng Rihardi (Unnes Law Journal, 2020)
The legal reform requires the fulfilment of disabilities human right is very important as a basis for strengthening the footing, so as to be able to respect, protect and fulfill the human rights of persons with disabilities without discrimination by upholding human value and dignity based on the Pancasila and the 1945 Constitution of the Republic Indonesia. The purpose of this study is to analyze the urgency of reforming human rights law of persons with disabilities and to analyze the model of legal reform to realize the fulfillment of human rights of persons with disabilities. This research method uses a type of normative juridical research by studying the legal literature. The results showed that the urgency of reforming human rights law for persons with disabilities in terms of philosophical, sociological and juridical aspects. The model of legal reform has embodied the fulfillment of the human rights of persons with disabilities in the harmonization of policies consisting of several aspects of regulatory structuring, aspects of institutional structuring and aspects of legal culture development. So legal reform is able to manifest the human rights of persons with disabilities, in this case as a form of crystallization of noble values and human dignity that are more just, progressive, democratic, prosperous and non-discriminatory.